A Modified Elastic Foundation Beam Method for Analyzing Lateral Wall Deformation in Excavations with Cross Wall. (26th July 2021) - Li, Bo; Wang, Guihe; Jia, Cangqin; Ren, Jun; Lu, Gaofeng; Liu, Nannan
Abstract : Cross walls have been used as alternative auxiliary measures to protect buildings in some areas of Asia. Realizing the inadequacy of the classical Winkler foundation to predict the deflection of the diaphragm wall with cross wall, a modified Winkler foundation of the finite element method (MEFB) was formulated in this paper. Then, the MEFB method was verified through two excavation cases and applied in a new well-documented excavation history. Results showed that the wall deflection by the proposed method was line with the 3D numerical analysis and field observations but smaller than that of classical Winkler's elastic foundation (EFB) method. The maximum deformation calculated by the MEFB method was predicted to have a reduction of 40∼60% compared to those of the EFB method. Meanwhile, the wall deformation was minimum at the location of cross walls and reaches the maximum value at the midline between two cross walls. Besides, the plane strain ratio PSR d based on the MEFB method was defined to study the interval L, the embedded depth, and arrangement of cross walls. The results indicated the MEFB method was used successfully as a more accurate method than Winkler foundation and is simpler than 3D numerical analysis method for the engineering design of the diaphragm-cross wall system during excavation.